Global changes and natural disaster management : geo-information technologies - Pirasteh, Saied; Li, Jonathan (Springer, 2017)
This book presents ongoing research and ideas related to earth observations and global change, natural hazards and disaster management studies, with respect to geospatial information technology, remote sensing, and global navigation satellite systems. Readers will discover uses of advanced geospatial tools, spatiotemporal models, and earth observation systems. Chapters identify the international aspects of the coupled social, land and climate systems in global change studies, and consider such global challenges as agriculture monitoring, the smart city, and risk assessment. The work presented here has been carefully selected, edited, and peer reviewed in order to advance research and development, as well as to encourage innovative applications of Geomatics technologies in global change studies. The book will appeal not only to academicians, but also to professionals, politicians and decision makers who wish to learn from the very latest and most innovative, quality research in this area of global change and natural disaster management. Contributions are drawn from revised submissions based on state-of-the-art papers from the 7th GiT4NDM - 5th EOGC, 2015 event.